TINGKAT PENGETAHUAN PETANI DALAM BUDIDAYA RUMPUT LAUT DI KELURAHAN WANDAKA KECAMATAN KULISUSU KABUPATEN BUTON UTARA - Neliati Neliati; Hartina Batoa; Rosmawaty Rosmawaty (Universitas Halu Oleo, 2023)
This study aims to determine the level of knowledge of farmers in seaweed cultivation in Wandaka Village, Kulisusu District, North Buton Regency. This research was conducted on all seaweed farmers in Wandaka Village. The selection of the research location was determined purposively with the consideration that it is an area that cultivates seaweed plants. As for this research, it was carried out from November to December 2022. The research results were analyzed using class intervals. The results showed that the level of knowledge of farmers in seaweed cultivation in Wandaka Village, Kulisusu District, North Buton Regency was in the high category as seen from farmers' knowledge in aspects of site selection, seed selection, planting, maintenance, pest and disease control, and harvesting. For aspects of farmers' knowledge in seaweed cultivation which are in the high category, namely in the aspects of site selection, selection of seeds, planting, and harvesting. As for the aspects of farmers' knowledge in seaweed cultivation which are in the medium category, namely aspects of maintenance and control of pests and diseases.